(WGS – 1984) إلى (Clarke – 1880)طریقة لتحویل الارتفاعات المقیسة بجهاز الاسِتقبال من الأقمار الصناعیة فی نِظام تَحدیدُ المواقِع العالَمیّ من - nan, nan (Iraqi Journal of Civil Engineering, 2010)
To find the Reduced Level ( R.L.) by traditional methods especially by the precise methods , for example using the level , needs time , hard work and then high cost . By using the new technology like Global Positioning System (GPS) reduces the time , the work and the cost .But the highest accuracy still remains for the traditional methods , and approximately the same accuracy could be reached by using precise surveying receivers of GPS with precise methods .Because there are no surveying receivers ,a navigation receiver (Trimble Geo XT handheld receiver ) is used in this research to get the (R.L.) (height above the Mean Sea Level ( the Fao in Iraq )) in the used system in Iraq (Clarke – 1880) in the area where the measurements are done( the University of Technology ). The (R.L.) of points in any other area in Iraq ,and by any other system in other country could be found in the same method . In this method , the changing factor from the measured heights (HAE) on the World Geodetic System (WGS – 1984 ) in any determined area by using the above receiver to heights on ( Clarke – 1880) in the same area can be found . When the changing factor of any area is found, the measured height of any point in this area (HAE) by using a receiver of (GPS) could be changed to the height in (Clarke – 1880 ). Then the (R.L.) of this point could be calculated by adding the Separation or the Geoidal Height between the Ellipsoid and the Geoid for the point , and the reverse is possible also.